Transversus Thoracis Muscle Plane Block in Paediatric Patients Who Underwent Minimally Invasive Closure of Transthoracic Ventricular Septal Defect: A Retrospective Study - Qiong Ling; Shuhua Zhao; Yongyong Shi; Xiangyu Li; Ping Li; Gaofeng Zhao; Qianqian Zhu (Pain Research and Management)
Objective. Minimally invasive closure of transthoracic ventricular septal defect (VSD) has been widely used in paediatric patients. This retrospective study aimed to explore the use of transversus thoracis muscle plane block (TTMPB) in the minimally invasive closure of transthoracic VSD in paediatric patients. Methods. From September 28, 2017, to July 25, 2022, a total of 119 paediatric patients scheduled for minimally invasive transthoracic VSD closure were considered for inclusion. Results. In total, 110 patients were included in the final analysis. Perioperative fentanyl consumption of the TTMPB group was not different from that of the non-TTMPB group (5.90 ± 1.32 μg/kg vs. 6.25 ± 1.74 μg/kg, p = 0.473). Both the time to extubation and postanesthesia care unit (PACU) stay were significantly shorter in the TTMPB group than in the non-TTMPB group (10.94 ± 10.31 min vs. 35.03 ± 23.52 min for extubation, and 42.55 ± 16.83 min vs. 59.98 ± 27.94 min for PACU stay, both p < 0.001). Furthermore, the postoperative paediatric intensive care unit (PICU) stay in the TTMPB group was significantly shorter than in the non-TTMPB group (1.04 ± 0.28 d vs. 1.34 ± 1.05 d, p = 0.005). Multivariate analysis demonstrated that TTMPB was significantly associated with shorter time to extubation (p < 0.001) and PACU stay (p = 0.001) but not postoperative PICU stay (p = 0.094). Discussion. This study showed that TTMPB was a beneficial and safe regional anaesthesia technique for paediatric patients who underwent minimally invasive closure of transthoracic VSD, although prospective randomized controlled trials are needed to confirm the results.